The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1073/pnas.0711303105
|View full text |Cite
|
Sign up to set email alerts
|

Diverse syntrophic partnerships from deep-sea methane vents revealed by direct cell capture and metagenomics

Abstract: Microorganisms play a fundamental role in the cycling of nutrients and energy on our planet. A common strategy for many microorganisms mediating biogeochemical cycles in anoxic environments is syntrophy, frequently necessitating close spatial proximity between microbial partners. We are only now beginning to fully appreciate the diversity and pervasiveness of microbial partnerships in nature, the majority of which cannot be replicated in the laboratory. One notable example of such cooperation is the interspeci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
272
1
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(294 citation statements)
references
References 38 publications
18
272
1
3
Order By: Relevance
“…For those cases, where the interaction partners have been studied in more detail, characteristic features such as the loss of essential biosynthetic functions (McInerney et al, 2007) or the formation of physical attachment structures (Ishii et al, 2005;Wanner et al, 2008) have been reported that may have arisen as specific adaptations to the symbiotic lifestyle. Unfortunately, the obligate interdependence of both partners makes it often difficult to study this type of interactions under laboratory conditions (Nauhaus et al, 2002;Pernthaler et al, 2008;McCutcheon and Moran, 2012). As a consequence, many open questions remain regarding the ecological and evolutionary consequences of entering into such an obligate cross-feeding interaction.…”
Section: Introductionmentioning
confidence: 99%
“…For those cases, where the interaction partners have been studied in more detail, characteristic features such as the loss of essential biosynthetic functions (McInerney et al, 2007) or the formation of physical attachment structures (Ishii et al, 2005;Wanner et al, 2008) have been reported that may have arisen as specific adaptations to the symbiotic lifestyle. Unfortunately, the obligate interdependence of both partners makes it often difficult to study this type of interactions under laboratory conditions (Nauhaus et al, 2002;Pernthaler et al, 2008;McCutcheon and Moran, 2012). As a consequence, many open questions remain regarding the ecological and evolutionary consequences of entering into such an obligate cross-feeding interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have characterized the composition and ecological role of microorganisms in methanecontaining marine sediments around the world (Inagaki et al, 2006;Heijs et al, 2007;Parkes et al, 2007;Pernthaler et al, 2008;Wegener et al, 2008;Harrison et al, 2009;Hamdan et al, 2012). These works assist in understanding the biological controls on oceanic methane and may contribute to establishing baselines to monitor change in marine sediments.…”
Section: Introductionmentioning
confidence: 99%
“…Another group, ANME-3, occurs for instance at Haakon Mosby Mud Volcano (Niemann et al, 2006; in situ temperature À1.5 1C) and the Eastern Mediterranean seepages (Omoregie et al, 2008;14 1C). Cells of both groups form dense consortia with specific bacterial phylotypes clustering with sulfate-reducing Deltaproteobacteria (most often within Desulfosarcinales, Seep-SRB-1a; Schreiber et al, 2010) or relatives of Desulfobulbus Lösekann et al, 2007;Pernthaler et al, 2008;Schreiber et al, 2010), respectively. A third phylogenetic group, ANME-1, is dominant in the microbial mats covering chimney structures at methane seeps in the Black Sea (Michaelis et al, 2002; in situ temperature of B10 1C), and in several diffusive methane interfaces (Thomsen et al, 2001;Lanoil et al, 2005;Harrison et al, 2009;Aquilina et al, 2010).…”
Section: Introductionmentioning
confidence: 99%